Pengaruh Kualitas Pelayanan, Fasilitas dan Ketersediaan Produk terhadap Kepuasan Pelanggan pada Perumda Air Minum Tirta Bahari Kota Tegal - Irfan Budi Prakoso; Hendri Sucipto; Azizah Indriyani; Syarieful Ikhwan (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the influence of Service Quality, Facilities, and Product Availability on customer satisfaction at Perumda Air Minum Tirta Bahari, Tegal City. Using a quantitative approach, the study involved 100 respondents from a population of 38,277. The results show that Service Quality (X1) significantly affects Customer Satisfaction (Y), with a t-count of 4.032 > t-table of 1.971 and a significance value of 0.034 < 0.05. This indicates a positive and significant relationship. Meanwhile, Facilities (X2) have no significant effect on Customer Satisfaction, as shown by a t-count of 0.418 < 1.971 and a significance value of 0.677 > 0.05. Product Availability (X3), however, significantly influences Customer Satisfaction, with a t-count of 4.597 > 1.971 and a significance value of 0.000 < 0.05. Furthermore, the simultaneous test (F-test) shows that all three variables—Service Quality, Facilities, and Product Availability—have a positive and significant effect on Customer Satisfaction, with an F-value of 9.415 > F-table of 2.649 and a significance value of 0.000 < 0.05. The coefficient of determination (Adjusted R Square) is 0.612, indicating that 61.2% of the variation in customer satisfaction is explained by the three independent variables, while the remaining 38.8% is influenced by other factors not included in the model. Overall, Service Quality and Product Availability are key factors in enhancing customer satisfaction at the organization.